2022
DOI: 10.1172/jci.insight.155296
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17-mediated EGFR ligand shedding directs macrophage-promoted cancer cell invasion

Abstract: Macrophages in the tumor microenvironment have a significant impact on tumor progression.Depending on the signaling environment in the tumor, macrophages can either support or constrain tumor progression. It is therefore of therapeutic interest to identify the tumor-derived factors that control macrophage education. With this aim, we correlated the expression of ADAM proteases, which are key mediators of cell-cell signaling, to the expression of pro-tumorigenic macrophage markers in human cancer cohorts. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…ADAM17-mediated JAM-A/ FIIR shedding is responsible for aging-related abnormal endothelial remodeling (156). However, other substrates, like EGFR ligands (17,97,180), E-cadherin (124), VLDLR (4), IL-11R (5), CD137 (94), P75 (11), GPIBa (6), HPP1 (119), and NRG1 (10) are precursor proteins or fusion proteins that can yield active components or soluble active receptors only after cleavage and release by ADAM17 (Figure 2). Evidence suggests that ADAM17 promotes tumor-associated macrophage polarization and angiotensin II-mediated pro-growth and promigration signals by shedding EGFR ligands, including heparinbinding EGF-like growth factor (HB-EGF) and AREG (members of the EGF family), from the cell membrane (17,32).…”
Section: Adam17 Mediates Substrate Shedding Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…ADAM17-mediated JAM-A/ FIIR shedding is responsible for aging-related abnormal endothelial remodeling (156). However, other substrates, like EGFR ligands (17,97,180), E-cadherin (124), VLDLR (4), IL-11R (5), CD137 (94), P75 (11), GPIBa (6), HPP1 (119), and NRG1 (10) are precursor proteins or fusion proteins that can yield active components or soluble active receptors only after cleavage and release by ADAM17 (Figure 2). Evidence suggests that ADAM17 promotes tumor-associated macrophage polarization and angiotensin II-mediated pro-growth and promigration signals by shedding EGFR ligands, including heparinbinding EGF-like growth factor (HB-EGF) and AREG (members of the EGF family), from the cell membrane (17,32).…”
Section: Adam17 Mediates Substrate Shedding Activitymentioning
confidence: 99%
“…Our previous study showed that the expression of ADAM17 was associated with infiltration of multiple immune cells, including macrophages (20), in TCGA pan-cancer samples and yet the specific regulatory mechanism of ADAM17 is unknown. Recently, Gnosa et al have revealed the positive roles of ADAM17 in regulating the polarization of TAMs (17). By using bioinformatics analysis based on the TCGA dataset and immunohistochemical analysis from triple-negative breast cancer cohort, the authors first confirmed that highly expressed ADAM17 in tumors is positively correlated with tumorigenic macrophage markers CD163 or CD206.…”
Section: Regulation Of Macrophages By Adam17mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that it might be possible to screen for molecules that selectively affect the orientation or presentation of the cleavage site(s) of EGFR ligands and other substrate proteins to ADAM17/iR2. This could help block the activity of EGFR ligands implicated in cancer and inflammation (e.g., AREG, EREG, [ 48 , 49 , 50 , 51 , 52 ]) without affecting the function of TGFα in protection of the skin and intestinal barrier [ 13 , 16 , 17 ]. This, in turn, could provide novel treatment options for diseases that depend on the dysregulated processing of specific EGFR ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The protumorigenic role of ADAMs has been further confirmed in vitro and in murine cancer models, where studies have shown a role in supporting tumor growth and metastasis 15‐17 . Although the implication of ADAMs in cell‐ECM and cell‐cell interactions has been shown in vitro, 18,19 their role in the crosstalk between cancer cells and the TME in murine cancer models is scarcely explored 20‐22 …”
Section: Introductionmentioning
confidence: 99%